2022
DOI: 10.1186/s12889-022-14704-6
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco chewing and associated factors among a vulnerable youth population in Sri Lanka

Abstract: Background Tobacco in any form kills millions of people every year. Tobacco addiction among youth shows an increasing trend while smokeless type is becoming more common. This study aimed to describe the lifestyle of chewing smokeless tobacco among a group of high-risk youth population in Sri Lanka. Methods A descriptive cross-sectional study was conducted among a sample of 1431 youths aged between 15 to 24 years residing in urban slums in Colombo S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Third, national household surveys may not capture high‐risk demographic and occupation groups smoked and ST use, as declining population trends could skew the risky health‐related behaviours towards high‐risk groups 18,41 . Supporting this notion, a recent study reported an alarming prevalence of current ST chewing among urban slum dwelling youth aged 15–24 years, which was 44.9% 45 . Of those ST users, 90.8% were males 45 .…”
Section: Differences Between Districts In the Distribution Of Oral Ca...mentioning
confidence: 99%
See 2 more Smart Citations
“…Third, national household surveys may not capture high‐risk demographic and occupation groups smoked and ST use, as declining population trends could skew the risky health‐related behaviours towards high‐risk groups 18,41 . Supporting this notion, a recent study reported an alarming prevalence of current ST chewing among urban slum dwelling youth aged 15–24 years, which was 44.9% 45 . Of those ST users, 90.8% were males 45 .…”
Section: Differences Between Districts In the Distribution Of Oral Ca...mentioning
confidence: 99%
“…18,41 Supporting this notion, a recent study reported an alarming prevalence of current ST chewing among urban slum dwelling youth aged 15-24 years, which was 44.9%. 45 Of those ST users, 90.8% were males. 45 ST comprised betel quid and commercially prepared tobacco and arecanut products.…”
Section: Increasing National Trends Of Oral Cancer Incidence Rates Ve...mentioning
confidence: 99%
See 1 more Smart Citation
“…This growth offers a unique opportunity to explore the potential of social media on oral health promotion among Sri Lankan adults. Supported by existing evidence on the prevalence of oral health problems in Sri Lanka [33][34][35], and given the influence of social media on health behaviours, the promotion of oral health via social media platforms may be considered as an important method, and its use seems to be a way forward [36,37]. Apart from that, real time engagement and feedback from dental professionals on oral health information on social media platforms, bridging information gaps on oral health and formulating effective future strategies in prevention of oral diseases have been very successful [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of detecting issues early goes beyond the individual well-being. It also plays a role in public health efforts to reduce the impact of oral cancers (7,8). Discovering problems at a stage not only benefits oral health but also has a significant impact on one's overall quality of life.…”
Section: Introductionmentioning
confidence: 99%